'It takes three to tango': new inter-institutional dynamics in managing major crisis reform. Issue 9 (2nd September 2022) - Smeets, Sandrino; Beach, Derek
ABSTRACT: This paper provides an in-depth reconstruction of the (failed) reform of the EU's Common European Asylum System. Even though this was essentially a legislative process, it was characterized by extensive European Council involvement. In fact, the European Council is commonly blamed for the lack of progress in EU reform. Divisions at the level of the Heads and an insistence on consensus made it impossible for the machine room to proceed with the dossier. We challenge this view, by looking at the interplay between the European Council, Council (of Ministers) and Commission. We argue that the effectiveness of European Council involvement crucially depends on the actions of these two institutions. Involvement of the Heads can propel, paralyze or derail EU decision-making, depending on when and how they are brought into play. The Council and Commission play a crucial role by anticipating, setting the scene for and providing the follow-up to European Council involvement.